Analysis Influence Management Quality Service to Satisfaction Guests at Star Hotels - Rismanto, Malik (Politeknik Siber Cerdika Internasional, 2024)
In industry very good hospitality competitive , satisfaction visitor become factor the main thing that determines success and sustainability star hotel business . Quality the services provided by the hotel are very play a role in to form perception guests and, ultimately , determine level satisfaction they . Research This aiming For analyze influence various dimensions quality services , including reliability , assurance , responsiveness , empathy , and cleanliness , towards satisfaction guest at a star hotel post- COVID-19 pandemic. Research This use approach quantitative with design descriptive-analytic . Data collected through questionnaire distributed? to guests who have stay at several star hotels , with criteria sample use purposive sampling method . Data analysis was carried out use multiple linear regression For identify contribution of each dimension quality service to satisfaction guest . Research results show that all dimensions quality service own influence significant to satisfaction guest , with cleanliness as the most dominant factor post-pandemic , followed by reliability and responsiveness . Dimensions empathy and reassurance also contribute , but with more value? low compared to factor cleanliness . This result indicates importance improvement quality services in the area of cleanliness and speed response in management strategy hotel services for fulfil expectation more and more guests high . Research This give guide for star hotels in strengthen Power competition through management quality optimal service .